Clamshell litter in Southeast Alaska - Tiffany Stephens; Ginny Eckert (Knowledge Network for Biocomplexity, 2019)
This dataset is composed of clamshell litter data, for which the cause of death of each clam was estimated using the physical condition of the valves. Shells were collected only if they were clean (without epibionts) and included the shell hinge. Shells were characterized as otter-cracked, crab-cracked or whole. Clamshell litter was collected at intertidal sites that included seagrass meadows (dominated by Zostera marina), in which three 100-m (year 2017) or 50-m (year 2018) transects were placed at different locations relative to the seagrass meadow: within the seagrass meadow, along the edge of the seagrass meadow, and outside the seagrass meadow. In 2017 and 2018, clamshell litter was collected at 36 different sites total in Southeast Alaska on Prince of Wales Island (n = 21 in 2017; n = 26 in 2018). These data directly compliment observations on the number of pits dug by sea otters in the intertidal while they foraged for clams, as well as qualitative descriptions of those sediments (which were collected along the same transects). Generally, these data were collected to compliment a larger, interdisciplinary project called APECS (Apex predators, Ecosystems, and Community Sustainability), the focus of which investigated the role that sea otters have on seagrass habitats, their ecological function, and influences on traditional and subsistence harvest of specified marine organisms (search "APECS_alaska" in KNB for all related datasets).